THERAPEUTIC EDUCATION: A NEW PERSPECTIVE ON CHILD DEVELOPMENTHOW THERAPEUTIC PRACTICES AND NEUROEDUCATION TRANSFORM THE CLASSROOM INTO A SPACE OF HEALING AND LEARNING (Editora Impacto Científico, 2025)
This article proposes a reflection on the practice of therapeutic education as an innovative and necessary path for child development in contemporary schools. Based on the fundamentals of neuroeducation, positive psychology, and integrative practices, it presents a perspective that goes beyond traditional teaching and recognizes children as whole beings: emotional, mental, physical, and spiritual. Based on experiences in the classroom, it discusses how simple techniques of mental reprogramming, conscious use of words, classical instrumental music, and affectionate intentionality can transform the school into a welcoming, healing, and meaningful learning environment. This work seeks to value the role of the educator as an active presence in the process of human formation and proposes practices that can be applied with lightness and depth in everyday school life.